THE MEDIATING EFFECT OF CUSTOMER SATISFACTION ON BEHAVIORAL INTENTIONS FOR ECOTOURISM EVIDENCE FROM BALI - Jaya, I Putu Gede Iwan Trisna; Hadi, I Gusti Ngurah Widya; Widiantari, Komang Sri (Universitas Brawijaya, Indonesia, 2018)
This study aims to measure the effect of destination image and perceived value, as well as customer satisfaction on the tourists' behavioral intentions in visiting the ecotourism object of Geopark Bangli. The research population is foreign tourists. The sample size was set at 179 people. The respondents were selected using convenience sampling technique from tourists who already know that Geopark Kintamani Bangli is an ecotourism attraction and gets an appreciation as a world cultural heritage. The data is processed and analyzed using SEM through PLS software. The results show that destination image, perceived value, and customer satisfaction have a positive and significant effect on the Behavioral Intentions. Perceived value has a higher correlation coefficient value when it is compared to the destination image and satisfaction. This indicates that managers of the attractions object and travel must adjust the cost spent by the tourists to the advantage they get. Other indicators of the perceived value that should be the material evaluation are functional value and emotional value. This indicates that tourists who visit the place considering the service and pleasure they received during the visiting.